Implementation of Intercultural Competence Through Arabic Language Learning for Students at Islamic Higher Education Institutions (PTKI) - Muhammad Ivan Alfian; Miftahul Huda (Al Hikmah: Journal of Education, 2023)
This study aims to describe the model, implementation, and evaluation of Arabic language learning reviewed from the perspective of intercultural competence at Islamic Higher Education Institutions, in this case IAIN Kudus and UIN Malang. The research approach used is a qualitative approach with a field study type that compares the implementation of Arabic language learning. Meanwhile, the data collected consisted of information from the administrators of the Arabic language institutions as well as documents on learning activities and observations of Arabic language learning. The results of this study are that 1) the model used in Arabic language learning at IAIN Kudus and UIN Malang is to organize intensive learning grouped according to ability, but there are differences in the weight of credits and the development of textbooks that reflect intercultural competence based on national policies and local wisdom, 2) the implementation of Arabic language learning at IAIN Kudus and UIN Malang is carried out simultaneously for all new students while still holding several supporting activities to achieve learning targets that continue to pay attention to intercultural competence in each stage of learning, and 3) the evaluation of Arabic language learning at IAIN Kudus and UIN Malang requires students to obtain a minimum score as a prerequisite for taking the final exam.